Perceived greenwashing and employee non-green behavior: the roles of prevention-focused green crafting and work alienation - Ibrahim A. Elshaer; Alaa M. S. Azazz; Mahmoud A. Mansour; Sameh Fayyad (Cogent Business & Management)
This research examines the influence of perceived greenwashing on employee non-green behavior, highlighting the key mediating roles of both prevention-focused green crafting and work alienation. Greenwashing has been progressively acknowledged as detrimental to corporate morales and sustainable workplace practices. Drawing from the theory of planned behavior and conservation of resources theories, this research posits that employees, upon perceiving greenwashing, are inclined towards engaging in non-green behaviors that contradict organizational environmental objectives. Additionally, the study delves into the mediation role of prevention-focused green crafting and work alienation in this context. Data was collected from 419 employees in the tourism industry and the data collected was analyzed using partial least square-structural equation modelling (PLS-SEM). The study’s findings indicated that perceived greenwashing is positively correlated with non-green behavior. Consumers may become suspicious of a company or product, which reduces their inclination to purchase. Additionally, the study’s findings demonstrated that prevention focused green crafting, and work alienation mediates the influence of perceived greenwashing on non-green behavior. Employees can further enhance their ‘green crafting’ by actively participating in new green initiatives or by adopting more green-assuming initiative behaviors. These insights highlight the importance of genuine corporate environmental efforts aimed at fostering sustainable workplace practices and mitigating the negative impacts of greenwashing.